Causes of Divorce in Muara Dua District Lhokseumawe City - Muchlis, Muchlis (Jurnal Al-Fikrah, 2023)
Divorce usually has causes. There is little chance of a divorce occurring when household conditions are good. Likewise in Muara Dua District. For this reason, it is necessary to investigate further what causes divorce in Muara Dua District, so that it can then be anticipated and a solution can be found. The aim of this research is to find out the causes of divorce in Muara Dua District, Lhokseumawe City, and what efforts are being made to reduce it. Through qualitative research, descriptive analysis techniques and inductive methods are the main techniques for tracing data and facts to be studied and finding answers to limited problem formulations. The results of the research are the causes of divorce in Muara Dua District, Lhokseumawe City, namely domestic violence (KDRT), economic problems, infidelity. Among these causes, the most dominant are domestic violence and economic problems. Because other reasons will ultimately lead to violence or economic problems. Efforts to reduce divorce in Muara Dua District, Lhokseumawe City include involving the role of religion. Apart from religion, there are efforts from the state to create various laws and regulations so that divorce can be minimized. Efforts from families and counselors are also considered important.